2007
DOI: 10.4081/ijas.2007.1s.327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding raw or extruded linseed on the ruminal ecosystem of sheep

Abstract: Polyunsaturated fatty acids affect bacterial and protozoal population, inducing important modifications in rumen metabolism. The aim of this study was to investigate the effect of linseed extrusion on in situ ruminal degradability and microbial number and distribution. Six ruminally fistulated sheep were divided in 3 groups and fed one of the following diets according to a replicated Latin square design: (a) control, based on mixed hay and maize grains; (b) as in (a) plus 130 g of grounded raw linseed; (c) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The intermediate level of dietary EL (and the limited daily intake of concentrate) was possibly able to provide the rumen environment with the optimal amount of lipids and, in the same time, did not impair dry matter degradability. It has been shown that at the highest EL concentration used in this study (20% of the concentrate) ruminal degradability and milk production can be negatively affected in dairy ewes [ 33 , 34 ]. Berthelot et al [ 16 ] evaluated the effects of EL-enriched diets administered to either Vendeen ewes or their lambs in 2 × 2 factorial arrangement using lower EL contents in both maternal (12.5%) and lamb (6%) concentrates compared to the EL levels used in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The intermediate level of dietary EL (and the limited daily intake of concentrate) was possibly able to provide the rumen environment with the optimal amount of lipids and, in the same time, did not impair dry matter degradability. It has been shown that at the highest EL concentration used in this study (20% of the concentrate) ruminal degradability and milk production can be negatively affected in dairy ewes [ 33 , 34 ]. Berthelot et al [ 16 ] evaluated the effects of EL-enriched diets administered to either Vendeen ewes or their lambs in 2 × 2 factorial arrangement using lower EL contents in both maternal (12.5%) and lamb (6%) concentrates compared to the EL levels used in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Vegetable oils have a more depressing effect on ruminal digestion than oilseeds, and processed oilseeds (extruded, rolled, micronized, roasted…) are more effective at increasing milk CLA content than raw seeds but less efficient than free oil (Doreau et al, 2009a;Doreau et al, 2009b). Extrusion, the most common technique used, has been proposed in order to decrease ruminal degradability and reduce the negative effects of PUFA on the ruminal environment (Mughetti et al, 2007).…”
Section: Introductionmentioning
confidence: 99%